Conserved MicroRNA Act Boldly During Sprout Development and Quality Formation in Pingyang Tezaocha (Camellia sinensis) - Zhao, Lei; Chen, Changsong; Wang, Yu; Shen, Jiazhi; Ding, Zhaotang (Frontiers in Genetics, 2019)
Tea tree [Camellia sinensis (L.) O. Kuntze] is an important leaf (sometimes tender stem)-using commercial plant with many medicinal uses. The development of newly sprouts would directly affect the yield and quality of tea product, especially significant for Pingyang Tezaocha (PYTZ) which takes up a large percent in the early spring tea market. MicroRNA (miRNA), particularly the conserved miRNAs, often position in the center of subtle and complex gene regulatory systems, precisely control the biological processes together with other factors in a spatio-temporal pattern. Here, quality-determined metabolites catechins, theanine and caffeine in PYTZ sprouts including buds (sBud), different development stages of leaves (sL1, sL2) and stems (sS1, sS2) were quantified. A total of 15 miRNA libraries of the same tissue with three repetitions for each were constructed to explore vital miRNAs during the biological processes of development and quality formation. We analyzed the whole miRNA profiles during the sprout development and defined conserved miRNA families in the tea plant. The differentially expressed miRNAs related to the expression profiles buds, leaves, and stems development stages were described. 21 miRNAs and eight miRNA-TF pairs that most likely to participate in regulating development, and at least two miRNA-TF-metabolite triplets that participate in both development and quality formation had been filtered. Our results indicated that conserved miRNA act boldly during important biological processes, they are (i) more likely to be linked with morphological function in primary metabolism during sprout development, and (ii) hold an important position in secondary metabolism during quality formation in tea plant, also (iii) coordinate with transcription factors in forming networks of complex multicellular organism regulation.